Exploiting the potential of extracellular vesicles as delivery vehicles for the treatment of melanoma - Hou, Chongchao; Wu, Qiang; Xu, Lizhou; Cui, Rongwei; Ou, Rongying; Li, Danyang; Xu, Yunsheng (Frontiers in Bioengineering and Biotechnology, 2022)
Melanoma, the most aggressive skin cancer that originated from genetic mutations in the melanocytes, is still a troublesome medical problem under the current therapeutic approaches, which include surgical resection, chemotherapy, photodynamic therapy, immunotherapy, biochemotherapy and targeted therapy. Nanotechnology has significantly contributed to the development of cancer treatment in the past few years, among which extracellular vesicles (EVs) are nanosized lipid bilayer vesicles secreted from almost all cells that play essential roles in many physiological and pathological processes. In terms of melanoma therapy, the unique physicochemical properties of EVs make them promising nanocarriers for drug transportation compared to other synthetic nanocarriers. Moreover, EVs can be further engineered to maximize their drug delivery potential. Herein, in this minireview, we gave a brief overview of EV-based drug delivery strategies for melanoma therapy, in which different therapeutics delivered via EVs were summarized. We also highlighted the current progress of the EV-based delivery platform for melanoma therapy in clinical trials. The obstacles to applying exosomes in clinical practice toward further translation of EVs melanoma therapy were also discussed at the end. In summary, EVs offer promising prospects for melanoma therapy, whilst the ways for unlocking EVs’ full potential in melanoma therapies should be further investigated by solving relevant issues which hamper EVs-based melanoma therapy translation in the future.